Function of private singing in instrumental music learning: A multiple case study of self-regulation and embodiment. (December 2019) - Casas-Mas, Amalia; López-Íñiguez, Guadalupe; Pozo, Juan Ignacio; Montero, Ignacio
The aim of this article is to explore a range of largely embodied vocalisations and sounds produced by learners of string instruments and how they relate to the potential self-regulatory use provided by such vocalisations. This type of "singing" while learning to play an instrument may have similarities to the use of private speech in other types of learning tasks. This report describes a multiple case study based on the naturalistic observation of learners playing string instruments in different situations. We observed private rehearsals by six adult guitarists from different music cultures (classical, flamenco and jazz) who had different approaches to learning (traditional and constructivist). In addition, we observed the one-to-one lessons of a constructivist cello teacher with a 7-year-old beginner and a 12-year-old student. All sessions were recorded. We applied the System for Analysing the Practice of Instrumental Lessons to the video lessons and/or practices and participant discourse for constant comparative analysis across all categories and participants. From the theoretical framework of private speech, we identified a set of qualities in private singing, such as whistling, humming, and guttural sounds, with different levels of audibility. Self-guidance and self-regulation appeared to be the functions underlying both psychomotor learning and reflective-emotional learning from an embodiment approach. Guitar learners from popular urban cultures seemed to use less explicit singing expression than classical guitar learners, the explicitness of which may be related to the instructional use of the notational system. In the one-to-one cello lessons, we observed a process of increasing internalisation from the younger to the older student. Both results are consistent with the literature on private speech, indicating that this process is a natural process of internalisation at higher literacy levels. Singing is not as frequent in music lessons as might be expected, and it is even less frequently used as a reflective tool or understood as an embodied process. The examples provided in this article shed light on the multiplicity of applications and on the potential benefits of private singing in instructional contexts as a powerful learning tool.